The investigation and publications registered in San Marcos - Luque Luque, Juvenal (2011)
The following text is intended to show the reader how much research ís done in San Marcos, who is done, what powets mote rescarch is done, like me kind of research OI scholarly acriviry rhat the university recognizes ro regísrer according tO tating scale preset. Has bccn used as a source ofinformarion on [he subjecr issued by rhe Consejo Superior de Investigaciones available ar web address. As a side issue slip sorne ideas about the role of rhe universiry,